Review Isolation Techniques Of The MIMO Antennas For Sub-6 - Mohammed Ibrahim, Ayman; Mohd Ibrahim, Imran; Shairi, Noor Azwan (Wydawnictwo SIGMA-NOT, 2021)
The MIMO antenna is at the core of the wireless technologies currently available. Designing MIMO antennas on a limited space requires different approaches to reduce mutual coupling, otherwise, efficiency, envelope correlation coefficients, diversity gain, radiation patterns, gain and isolation will be greatly affected. Various isolation techniques have been introduced in the past five years in the previous literature to improve the performance of MIMO antennas. This review paper shows an extensive thorough reported of the envelope correlation coefficient, efficiency, Isolation, size, number of ports and isolation techniques in compact MIMO antennas to various bands